2000
DOI: 10.1038/sj.sc.3100996
|View full text |Cite
|
Sign up to set email alerts
|

Early autonomic dysreflexia

Abstract: Introduction: During the stage of spinal shock the conventional view is that autonomic activity is abolished. Here, evidence is presented that autonomic activity is still present. Patients: Four patients with acute cord transactions are presented: one new case and three from the literature. De®nitions: The de®nitions of spinal shock and autonomic dysre¯exia are given. Methods: All four cases showed acute autonomic dysre¯exia between 7 and 31 days after acute cord transection at a stage when the tendon re¯exes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 7 publications
0
30
0
5
Order By: Relevance
“…This cut-off time was selected because the majority of patients who were discharged from the hospital at acute stage used indwelling urethral catheters; instead, we wanted to explore the relationship between bowel and bladder management methods, and AD at chronic stage. AD can occur at any time after injury even within the first few days 16,17 and commonly develops in patients with tetraplegia or high-level paraplegia at 3-4 months after the cord lesion; 18 (3) no pressure ulcerations, deep venous thrombosis, ureteral or renal stones or heterotopic ossification throughout hospitalization to exclude possible influence of these complications on cardiovascular condition.…”
Section: Methodsmentioning
confidence: 99%
“…This cut-off time was selected because the majority of patients who were discharged from the hospital at acute stage used indwelling urethral catheters; instead, we wanted to explore the relationship between bowel and bladder management methods, and AD at chronic stage. AD can occur at any time after injury even within the first few days 16,17 and commonly develops in patients with tetraplegia or high-level paraplegia at 3-4 months after the cord lesion; 18 (3) no pressure ulcerations, deep venous thrombosis, ureteral or renal stones or heterotopic ossification throughout hospitalization to exclude possible influence of these complications on cardiovascular condition.…”
Section: Methodsmentioning
confidence: 99%
“…This is usually due to a distended viscus (eg, bladder or bowel) acting as a stimulus causing massive sympathetic outflow below the zone of injury, which is unregulated by supraspinal input. One case report 79 suggested that autonomic dysreflexia may occur as early as 7 days after a complete injury, but the general time course of its development requires further study.…”
Section: Clinical Description 4-30 Daysmentioning
confidence: 99%
“…8 Previously, it was felt that the hypotensive episodes were confined to the acute period following SCI, and autonomic dysreflexia to the chronic phase of SCI. 6 However, it has also been shown that autonomic dysreflexia can present in the early phases of SCI, 23,24 and that orthostatic hypotension can persist for years, and often becomes worse with time. 25 Numerous investigators identified various possible mechanisms that are likely to be responsible for the abnormal sympathetic cardiovascular control following SCI (Table 1).…”
Section: Physiology and Neuroanatomy Of Cardiovascular Controlmentioning
confidence: 99%